Multimedia courseware learning: attractive simulation of fractions / Nur Alizafatin Rusli - Rusli, Nur Alizafatin (2014)
Attractive Simulation of Fractions is a Multimedia courseware that is developed as an added tool for primary school students at the age 10 years old to learn Mathematics with interesting and enjoyable way. This research focuses on Subtraction of Fraction in order to overcome the problem that faced by children that having low ability. The application also will overcome the children with low ability to become more understanding in the Fractions. The aim of this research is to identify the methods for fractions of primary school children for simulation of fractions learning style, to identify the requirement for primary school children for simulation of fractions learning style and to design* and develop the multimedia courseware for simulation of fractions learning. Combination of multimedia elements in education makes the student more concentrate to the learning. Through that, multimedia courseware makes the learning more interesting with the elements such as sound, text, image, and animation. With this, the simulation in this project will help the children become more understanding and reduce the educator time to teach the children. As the result, the low ability students can easily understand and attract to learn fraction. This closure would give many advantages to children, parents and educators.